THE INFLUENCE OF BLACKBOX AI LEARNING ON STUDENTS’ ENGLISH WRITING SKILL - Tantri Yunita; Yulia Agustina; Astrid Dwimaulani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the significant influence of using Blackbox AI onimproving students’ English writing skills. The purpose of this study was to determine thesignificant influence between the use of Blackbox AI and students' writing skillsThis research used a quasi-experimental design involving 54 eleventh-grade students at MA Al-Islamiyah Bebidas, divided into an experimental group (26 students) taught using Blackbox AI and a control group (28 students) taught using traditional methods. Data werecollected through pre-test, post-test, and perception questionnaire. The results showed thatthe experimental group obtained a higher mean score (M = 89.31) compared to the controlgroup (M = 69.57). An independent samples t-test (t = 14.54, p < 0.001) confirmed thesignificant influence of using Blackbox AI on students’ writing ability. In addition,students gave positive perceptions, especially on the improvement of vocabulary mastery,grammatical accuracy, and writing confidence. Thus, this research proves that Blackbox AIis an effective tool to improve students’ English writing skills as well as create moreengaging learning experiences.